(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In the Bukhara oasis, the use of low-mineral groundwater sources for irrigation and the use of water-saving irrigation methods for winter cereals have resulted in positive changes in the growth and development of grain in the case of seasonal irrigation with 50 kg of hydrogel crystals per hectare. 4000 m3 / ha.